2021
DOI: 10.3390/ijerph182010912
|View full text |Cite
|
Sign up to set email alerts
|

Association of BMI, Physical Activity with Academic Performance among Female Students of Health Colleges of King Khalid University, Saudi Arabia

Abstract: Body mass index (BMI) is an indicator to detect weight category and known to influence the academic achievements of students. The present study assesses the association of BMI, physical activity with academic performance among undergraduate female students of health colleges, King Khalid University (KKU). Responses from 379 participants were analyzed in the study. Data collection was done by administering an online questionnaire using the university website portal. The questionnaire consists of two sections: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
2
14
3
Order By: Relevance
“…The results were contrary to our expectations, as it is assumed that chronic diseases affect the performance of students, especially in practical training. These results disagree with the study by Alhazmi et al, 2021 revealed that an inverse relationship was observed between BMI and academic performance, showing participants within the normal BMI category achieved signi cantly higher GPAs. In contrast, physical activity directly in uenced the academic performance of the subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…The results were contrary to our expectations, as it is assumed that chronic diseases affect the performance of students, especially in practical training. These results disagree with the study by Alhazmi et al, 2021 revealed that an inverse relationship was observed between BMI and academic performance, showing participants within the normal BMI category achieved signi cantly higher GPAs. In contrast, physical activity directly in uenced the academic performance of the subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, PA levels positively affected GPA among medical students at King Saud University in Saudi Arabia [14]. Likewise, a study of female health college students at King Khaled University in Saudi Arabia demonstrated that PA levels were positively associated with AP [13]. While our study showed a significant difference in GPA among physically active females, multiple methodological tools differentiate it from the two studies at King Saud and King Khaled Universities.…”
Section: Figure 1 Comparison Of Grade Point Average Across Physical A...contrasting
confidence: 54%
“…According to one study in Pakistan, 4th-year medical students at Rawalpindi Medical University scored low grades because of the lack of PA [12]. Further, two studies in Saudi Arabia support the idea that PA positively affects AP [13,14]. However, no studies in Jeddah, Kingdom of Saudi Arabia (KSA) correlate PA with students' academic scores.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that physical activity helps achieve better academic performance through increased serotonin secretion, improved cerebral circulation, changes in hormone levels, and increased self-esteem (14). Other researchers have also found a positive correlation between the physical activity level and cognitive functioning, especially the working memory (15,16).…”
Section: Discussionmentioning
confidence: 83%